The Importance of Retrosynthesis in Organic Synthesis (London Journal of Research In Science: Natural and Formal, 2024)
The process of designing- an-effective synthesis plan for a target molecule remains a signifi1cant challenge in organic synthesis. Synthesis planning involves determining the steps to synthesize a desired molecule. Retrosynthesis, developed by Elias James Corey and recognized with a Nobel Prize in 1990, is a systematic approach that involves working backwards from- the target-molecule to identify the -starting materials-. Retrosynthetic analysis is a-- valuable technique but requires a comprehensive understanding of chemical substances, compound classes, reactions, and reaction conditions. This understanding enables chemists to effectively plan and analyze the synthesis of the target molecule. Through analyzing the target molecule and identifying possible disconnections, chemists can think creatively and devise innovative solutions for complex synthetic problems. This article serves as an introduction to retrosynthesis, highlighting its importance and fundamental theoretical concepts (strategies) that can be combined to plan the synthesis of organic compounds.
Keywords: Disconnections strategies; Organic synthesis; Retrosynthesis; Synthetic plan; Target molecule.1